Bioceramic production from giant purple barnacle (Megabalanus tintinnabulum) - (:unkn) unknown (Trans Tech Publications Ltd, 2015)
In this study the structural and chemical properties of barnacle shell based bioceramic materials (i.e. hydroxyapatite, whitlockite, monetite and other phases) were produced by using mechano-chemical (hot-plate) conversion method. Cleaned barnacle shells were ball milled down to <75μm in diameter. Differential thermal and gravimetric analyses (DTA/TGA) were performed to determine the exact CaCO3 content. Sample batches of 2g were prepared from the fine powders produced. For each batch, the required volume of an aqueous H3PO4 solution was calculated in order to set the stoichiometric molar ratio of Ca/P equal to 1.5 for β-tricalcium phosphate (β-TCP) or to 1.667 for hydroxyapatite (HA). The temperature was set to 80°C for 15 minutes to complete the process. After the titration of the equivalent amount of H3PO4 into the prepared solution, agitation was carried out on a hot-plate (i.e. mechano-chemical processing) for 8 hours. The sediments formed were dried and the resulting TCP and HA powders were calcined at 400°C and 800°C respectively. For complete characterization of the bioceramics produced, scanning electron microscopy (SEM), fourier transform infrared spectroscopy (FTIR) and x-ray diffraction (XRD) analyses were carried out. The current study proposes a simple, economic and time efficient method for nano-bioceramic production.
Keywords: Calcite; Hydroxyapatite; Marine creatures; Mechano-chemical conversion; Nano-bioceramics